Determination of acute toxicity and adverse effects of high doses of prolonged use of lithium ascorbate on Wistar rats - K. S. Ostrenko; I. S. Sardaryan; O. A. Gromova; E. M. Koloskov; A. V. Pronin; I. Yu. Torshin (Фармакокинетика и Фармакодинамика, 2016)
Toxicity study in male Wistar albino rats showed that the LD50 of Lithium ascorbate is 6,334 g/kg which refers the substance to grade 5 toxicity (practically non toxic). Accumulation ratio of Lithium ascorbate was found to be 14,8 thus indicating a Low cumulative effect and confirming Low toxicity. HistoLogicaL findings in animaLs treated with Lithium ascorbate daiLy for 30 days in doses cLose to LD50 indicate that an excess strain is exerted upon the neuroendocrine system (heterogeneity of ceLL eLements, signs of dystrophic changes) and, to a Lesser extent, upon the internaL organs. At the same time, after the subtoxic doses were ceased a partiaL restoration of functionaL activity of the organs invoLved was observed.